Hardiness dan Resiliensi Pada Pengangguran Dewasa Awal - Yulysma Eka Saputri; Nurul Khasanah; Rully Afrita Harlianty (Universitas Mercu Buana, 2025)
Unemployment in early adult can give rise to psychological dynamics. However, through the ability to survive, adapt, and bounce back, individuals can overcome these conditions. The purpose of this study was to determine the relationship between hardiness and poverty in early adulthood in Banten Province. The research design used a quantitative correlational method and a non-probability sampling technique using purposive sampling. The sample in this study was a decline in early adulthood totaling 100 respondents. The resilience measurement tool uses the theory of Connor & Davidson (2003) namely the modified Connor-Davidson Resilience Scale (CD-RISC) with a total of 25 valid items and a reliability coefficient value (α) = 0.911 and on hardiness using the Dispositional Resilience Scale: A Short Hardiness Scale (DRS-15) measuring tool developed by Bartone (1989) which has been modified consisting of 12 valid items with a reliability coefficient (α) = 0.803. The results of the correlation test obtained a significance value of 0.000 (p <0.05) and a correlation coefficient value (r) of 0.591 (p <0.01) obtained the results of early adult learning have high resilience 92% and high resilience 96% can be interpreted that there is a significant positive relationship between resilience and resilience.